Evaluation of the school health services (UKS) role trough the pattern of cooperation with the community health centers in creating a healthy and clean school environment - Fajar Dwi Wijayanto; Hedi Ardiyanto Hermawan (Jurnal Kependidikan Penelitian Inovasi Pembelajaran, 2023)
This study aims at analyzing the role of the School Health Services (UKS) through the cooperation of the Community Health Centers (Puskesmas) in creating a healthy school environment. This study used an observational method by designing a cross-sectional analysis to analyze the implementation of the School Health Services (UKS) Triad Programs in Elementary School Units in Imogiri District, Bantul Regency, Special Region of Yogyakarta, namely Kebonagung Elementary School, Nogosari Elementary School, and Pucung Elementary School. The research respondents were decided using a purposive sampling of school health business stakeholders from the education sector (office, school principals, teachers, and those in charge of UKS), the health sector, sub-district level government, and parents or guardians of students. SD Negeri Nogosari and SD Negeri Pucung were schools categorized as good in the management of the School Health Business Unit. These three public elementary schools have also collaborated with parents or guardians, Community Health Centers, and the surrounding community in implementing the School Health Services (UKS) Triad Programs.Keywords: Evaluation; School Health Services; Elementary Schools; Triad Programs